Analisis Faktor Penyebab Kecemasan Belajar Matematika Pada Siswa Sekolah Menengah Atas (SMA) - Siska Dwi Astiati, Siska; Ilham, Ilham (Lembaga Penelitian dan Pendidikan Mandala, 2023)
The purpose of this research is to look at the factors that cause anxiety in learning mathematics. This type of research is descriptive qualitative approach. The subjects of this study were students of class XII IPA Harapan High School, Wadukopa Village, Soromandi District. Retrieval of research data using questionnaires, interviews. The results of the study show that the anxiety of learning mathematics experienced by students of class XII IPA SMA Harapan is grouped into three parts, namely; students with high anxiety are influenced by the way the teacher explains the material they teach and environmental factors where students feel pressured when learning mathematics because learning is too monotonous causing students to feel bored quickly and causing students to feel afraid if their math scores do not match expectations. Factors causing anxiety Moderately assumes that mathematics is a scary subject because it is related to reasoning, analyzing, and solving problems systematically. Whereas Low anxiety feels uncomfortable in mathematics and considers mathematics to be a very frightening subject, resulting in students not liking mathematics.